Comparison of Changes in Intraocular Pressure after Subtenon and Peribulbar Local Anaesthesia for Phacoemulsification - Mumtaz Alam, Sher Akbar Khan, Mir Ali Shah, Ibrar Hussain, Faisal Nawaz (Pakistan Journal of Ophthalmology, 2017)
Objective: To compare the changes in intraocular pressure after subtenon and peribulbar local anesthesia in patients undergoing phacoemulsification.. Study design: Prospective interventional case series. Place and duration of study: The study was conducted at the Department of Ophthalmology, Khyber Teaching Hospital Peshawar. The duration of study was one year i.e. from October 2009 to October 2010. Materials and methods: The patients were divided into two groups. Group “A” received subtenon anesthesia and group “B” received peribulbar anesthesia. Intraocular pressure was measured just before, after 1 minute and 10 minutes after the administration of anesthesia. All the data were recorded on a proforma. SPSS-20 was used for data analysis. Results: There were 152 patients in each group. The 2 groups were similar in terms of age (P value = 0.83) and gender (P value = 0.73). There was no difference in mean intraocular pressure between two groups just before injection (P value = 0.72). There was a greater rise in mean intraocular pressure just after injection in group “B” as compared to group “A” (P value < 0.0001); in both groups the mean intraocular pressure declined to its base level after 10 minutes of injection (P value = 0.52). Conclusion: Subtenon anesthesia leads to little rise in intraocular pressure as compared to peribulbar anesthesia immediately after the injection. However 10 minutes after injection the intraocular pressure declines to its base level in both groups. Key words: subtenon anaesthesia, peribulbar anaesthesia, intraocular pressure.